Self care under the perception of the mental health nursing professionals - Silva, Adão Ademir; Terra, Malene Gomes; Freitas, Fernanda Franceschi de; Ely, Gabriela Zenatti; Mostardeiro, Sadja Cristina Tassinari de Souza (Rev Rene, 2013)
This qualitative research aimed at understanding the self care of the mental health nursing professionals. Ten nursing professionals of the mental health team of a psychiatric unit of a university hospital in the State of Rio Grande do Sul, Brazil, were interviewed from September to December 2010. The research data were collected through interviews and analyzed based on the referential phenomenology. The research result unveiled these categories: situations experienced in the encounter with the other and the possibilities of self-care in mental health. We conclude that self-care starts from the perception of the intersubjective encounter as a way to build relationships and human interactions which are more sensitive and open to dialogue with one another. DOI:https://doi.org/10.15253/2175-6783.2013000600005